Analisis Wilayah Kecamatan Potensial Melalui Pendekatan Tipologi Klassen di Kabupaten Ende - Estherlina Sagajoka (ANALISIS, 2020)
This study aims to determine the comparison of the results of the inequality analysis of economic development between districts / cities in the province of East Nusa Tenggara for the period of 2013-2018. The method used in this research is quantitative descriptive analysis using the Williamson index, and Theil Entropy Index, using time data per capita PDRB series and population data for each district / city in 2013-2018. The Williamson Index analysis results show that the economic development sector inequality in 21 districts in NTT province is very evenly distributed (low inequality) except for the city of Kupang, which has an Williamson Index value of 1.49 other than districts in NTT province in the period 2013-2018. The Intra Index Analysis Results show spatial inequality within the regency. The city of Nusa Tenggara Timur province is fairly evenly distributed within the regency except the city of Kupang shows an unequal inequality compared to 21 other districts. Through the Theil Entropy Index calculation of development inequality between 21 regencies and Kupang tend to widen (divergence) which has Theil Index of 798,15, while the other 21 districts in the 2013-2018 period have the Theil Entropy Index Index 211,26 for Regencies and TTS 201,11, while other districts have an index numberbelow 200.